Effect of divalent ions (A = Ca, Ba and Sr) substitution in La-A-Mn-O manganite on structural, magnetic and electrical transport properties - Lim, Kean Pah; Ng, Siau Wei; Shaari, Abdul Halim; Chen, Soo Kien; Wong, Jen Kuen (Science Publications, 2009)
Problem statement: Microstructure of the grain will influence the properties of a polycrystalline manganites when different dopant is introduced. In this work, an effort had been made to investigate the influence of Ca, Ba and Sr substitution in La site. Approach: Polycrystalline manganites compound of La0.67A0.33MnO3 where A = Ba, Sr and Ca had been prepared via conventional solid-state reaction method. The structure, microstructure, magnetic and electrical properties had been investigated using XRD, SEM, VSM and four-point probe techniques. Results: XRD spectrums showed that LBMO and LCMO were in single-phase orthorhombic structure whereas LSMO was rhombohedral structure. Scanning electron micrographs showed that LSMO had smaller average grain size as compared to LBMO. However, for LCMO, there was no clear grain boundary that can be observed and all the grains were well connected. The difference in the microstructure image might be due to the variance A-site cation that differs in grain growth. The Curie temperature, Tc of LBMO and LSMO was 343.0 and 363.5 K, respectively. But the Tc for LCMO was lower then 300 K. The Tp for LCMO was 215 K while it was near or above 300K for LBMO and LSMO. All samples showed extrinsic Magnetoresistance (MR) effect. Higher MR was observed well below Tc or Tp where MR value increased monotonically with the decrease of temperature. This was associated with the different grain and grain boundary formation when different cation was substituted. LCMO displayed the highest low-field MR value (-15.82% at 0.2 T, 90 K) and high-field MR (-25.60% at 1 T, 300 K). Conclusion: Hence, electrical and magnetic transition temperature (Tp and Tc) were affected by the average A-site cation radius.